Pilot Study Using the Augmented Reality Sandbox to Teach Topographic Maps and Surficial Processes in Introductory Geology Labs. Issue 3 (19th August 2016) - Woods, Terri L.; Reed, Sarah; Hsi, Sherry; Woods, John A.; Woods, Michael R.
ABSTRACT: Spatial thinking is often challenging for introductory geology students. A pilot study using the Augmented Reality sandbox (AR sandbox) suggests it can be a powerful tool for bridging the gap between two-dimensional (2D) representations and real landscapes, as well as enhancing the spatial thinking and modeling abilities of students. The AR sandbox involves a real box of sand with virtual contour lines and a water flow model created using a three-dimensional (3D) scanning camera, visualization software, and a projector. It was used in undergraduate, physical geology courses to teach topographic maps and surficial features and processes. The instructor demonstrated topographic concepts (contour lines, topographic profiles, etc.), and students engaged in model building of coastal and fluvial environments (drainage basins, cutoffs, longshore transport, sea-level rise, spits, flooding, etc.). The virtual water flow model was used to illustrate water flow dynamics on surface features. With the AR sandbox connected to a computer monitor, students could simultaneously see 3D landscapes in the sandbox and their corresponding 2D images on the monitor. Students used camera phones to capture landscape models they built and submitted them via e-mail for grading. Exit surveys indicated students were overwhelmingly positive (97%) in their perception of how the AR sandbox improved their understanding of learning objectives. They also preferred AR sandbox activities when compared to traditional laboratories that used only topographic maps. Effective classroom use of the AR sandbox required developing student-modeling exercises that took advantage of real-time feedback, virtual water, and physical modeling activities. While data are limited and more research is needed, real-time feedback on student models by both the students and the instructor suggests sandbox models are particularly useful for dispelling student misconceptions.